ANTIFUNGAL EFFECT OF TURMERIC EXTRACT (Curcuma domestica) IN LIQUID SOAP FORMULATION AGAINST THE GROWTH OF Malassezia furfur ATCC 14521 - Mursyida, Eliya; Tanjung, Anellia Putri (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Turmeric (Curcuma domestica) has been identified as a potential natural antifungal agent due to its curcuminoids and essential oils. Malassezia furfur, a lipophilic fungus, is commonly found on human skin but can become pathogenic, causing Pityriasis versicolor. This study aimed to evaluate the antifungal activity of turmeric extract in a liquid soap formulation against Malassezia furfur. A post-test only with control group design was used, employing the well-diffusion method to assess antifungal efficacy. Turmeric extract was incorporated into liquid soap at concentrations of 10%, 15%, and 20%, with positive (commercial antifungal soap) and negative (soap base) controls. The inhibition zones were measured using a vernier caliper, and data were analyzed using One-Way ANOVA followed by post hoc Bonferroni testing. Results showed that all formulations met the Indonesian National Standards (SNI). The highest inhibition zone was observed at 20% concentration (17,46 mm), while the lowest was at 10% concentration (15,80 mm). ANOVA analysis confirmed significant differences between groups (p < 0,05). The study concludes that turmeric extract in liquid soap formulations demonstrates antifungal activity against Malassezia furfur and has potential as a natural alternative to synthetic antifungal agents.